Efektivitas Stimulasi Dini Dan Pemberian Makanan Tambahan (PMT) Terhadap Perkembangan Balita Kurus - Baiq Eka Putri Saudia (Poltekkes Kemenkes Mataram, 2020)
Background : Wasting is an acute nutritional problem as a result of lack of food intake which can reduce the productivity and quality of human resource development. In child development, there is a critical period when stimulation is needed for potential develops under age of 5 years called the golden age of development. Provision of additional food is intended to fill the nutritional needs of children and is expected to help develop. Objectives : This study aimed to analyze the effect of additional foods and early stimulation on the development of wasting child. Methods : The design in this study uses the Pre Experimental Design with the One Shot Case Study approach. Data analysis using univariate analysis is by analyzing the level of development with KPSP. Bivariate analysis in this study was used to determine the effect of additional foods and Early Stimulation on the Development of Wasting Child in the Public Health Center of Gunung Sari by conducting an analysis test of the Kruskal Wallis test processed in the computer program. Results : The results showed that there was an effect after additional foods and early stimulation given on the development of wasting child (p = 0.012). Among the three variables used, the combination intervention of additional foods and early stimulation had the best influence compared to the other two interventions. Conclusion : There is an effect after supplementary feeding and early simulation on the development of underweight children.